The Uniqueness of Managerial Competency Model in Indonesian Districts and Cities - Ira Irawati; MD. Enjat Munajat (Policy & Governance Review, 2023)
Managerial competency is a fascinating field to continue to develop and study until now. UNDP is still formulating the Competency Framework until 2030 (United Nations, 2018). The popularity of this field stems from the flexibility and dynamic nature of organizational practices that have been born due to global development. Managerial competencies have three components: conceptual skills, human resources skills, and technical skills. In Indonesia, city governments find it difficult to determine the right person based on managerial competence, so the wrong person is placed to occupy a strategic position. Therefore, this research wants to determine the right proportion of the three components of managerial competency and their indicators. That was the background of this study: analyzing the proportion of these skills by taking case studies in 2 regions in Indonesia, namely the Tasikmalaya Regency and Serang City. This study sought to find what managerial competency models apply in Indonesia, especially those represented by the two cities/regencies in Indonesia. This study used mixed methods: quantitative methods for distributing questionnaires to Echelon/ Class III and IV officials in the two cities and qualitative for expert group discussions to validate that would strengthen the analysis. The time needed for this research is about one year (around February 2019- August 2020). The contribution of this research shows that when an area uses an ideal competency managerial model, it is easier to achieve its vision and mission. The study results indicate that the Tasikmalaya Regency is quite good in its managerial competence selection process. It can be seen from the proportion of the three sets of dynamically dispersed managerial competencies compared to the ideal model, in contrast to Serang City, which is still far from ideal conditions. Serang City must improve its managerial competency model to make it more ideal. This is needed so that organizations can deal with changing times, which tend to be exponential to maximize performance achievements.